The Existence of Balinese Female Dancers in Tisna's Ni Rawit Ceti Penjual Orang, Rusmini's Tarian Bumi, and Arnada's Jejak Dedari - Sukmawati, Ni Luh Ayu (Lakon : Jurnal Kajian Sastra dan Budaya, 2024)
This qualitative research aims to reveal how Balinese female dancers have existed by dancing in each era depicted in three novels namely Ni Rawit Ceti Penjual Orang (1935) by A.A. Pandji Tisna, (2) Tarian Bumi (2000) by Oka Rusmini, and (3) Jejak Dedari (2016) by Erwin Arnada. Structural-narrative theory by A.J. Greimas and Simone de Beauvoir's existentialist feminism approach was used to dissect the three novels. From the analysis, some differences describe the characteristics of Balinese female dancers in each era. In the novel Ni Rawit Ceti Penjual Orang as a marker of the postcolonial era, female dancers have not been able to reach their existence because of tradition dominated by men. In contrast, in Tarian Bumi and Jejak Dedari as a remark of the 2000s, Balinese female dancers can achieve their existence with the help and motivation of the surrounding community of figures. Thus, it shows the progress in the way of Balinese society towards the existence of Balinese female dancers from time to time.